2019
DOI: 10.1038/s41598-019-48836-4
|View full text |Cite
|
Sign up to set email alerts
|

Local pulses of electrical potential can induce long-range transient excitations in self-aligned molecular films

Abstract: Natural liquids can contain self-aligned molecules (such as liquid crystals and biological membranes) which give them unique properties of anisotropic diffusion, coupling between the molecular orientation and flow, etc. Here, we describe the observation of new phenomena in those materials: long-distance transport and molecular orientation waves that are induced by pulses of spatially localized electrical potential. As a result, the morphological properties of the material are significantly altered well beyond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…This reorientation, in turn, can cause hydrodynamic flow; so-called backflow effects can be observed. As already explained by the authors in [17], this effect can support the observed material transport only at the early stage of the process since the characteristic relaxation time of the process is much shorter than the relaxation time of the director.…”
Section: Theorysupporting
confidence: 58%
See 4 more Smart Citations
“…This reorientation, in turn, can cause hydrodynamic flow; so-called backflow effects can be observed. As already explained by the authors in [17], this effect can support the observed material transport only at the early stage of the process since the characteristic relaxation time of the process is much shorter than the relaxation time of the director.…”
Section: Theorysupporting
confidence: 58%
“…A pressure gradient, which in this case is caused by the local dielectric torque-induced reduction of the effective molecular volume, will result in a flow of the NLC. The authors in [17] observed the LC reorientation near the boundaries between two parts of the LC cell. This reorientation, in turn, can cause hydrodynamic flow; so-called backflow effects can be observed.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations